PERLINDUNGAN KONSUMEN TERHADAP IKLAN YANG MENGANDUNG JANJI BELUM PASTI DALAM PERDAGANGAN ELEKTRONIK: STUDI TERHADAP IKLAN VITAMIN ANAK GENEROS: Consumer Protection Against Advertisements Containing Uncertain Promises in Electronic Commerce: A Study of Advertisements for Generos Children's Vitamins - Abigail Herlin Wibowo Putri; Sharda Abrianti (AMICUS CURIAE, 2025)
There are still many advertisements displayed via electronic commerce in Indonesia that do not comply with the regulations relating to advertising. One of them is an advertisement for "Generos children's vitamins" which claims to be able to overcome speech delays in children. This is detrimental to consumers as a result of the claims contained in advertising and cannot operate scientifically. Identification problem raised is whether the advertisement for "Generos children's vitamins" is included in the category of advertisements that contain uncertain promises and  based on consumer protection law. This research uses normative and descriptive methods, data sources use primary and secondary data, qualitative data analysis, and conclusions are drawn using deductive reasoning. The results and the conclusion of this research analysis are an explanation regarding the advertisement "Generos children's vitamins" which can be classified as an advertisement that contains uncertain promises.